A Chemically Engineered Porous Copper Matrix with Cylindrical Core–Shell Skeleton as a Stable Host for Metallic Sodium Anodes. (28th May 2018) - Wang, Chuanlong; Wang, Huan; Matios, Edward; Hu, Xiaofei; Li, Weiyang
Abstract: Sodium (Na) metal is the most promising alternative for lithium metal as anode for the next‐generation energy storage systems. However, its practical implementation is hindered by the huge volume change and severe Na metal dendrite growth during electrochemical stripping/plating. Herein, the use of a chemically engineered porous copper (Cu) matrix as a stable host for metallic Na anode is presented. By treating the commercial Cu foam through a facile and cost‐effective method, a composite matrix consists of cylindrical core–shell skeleton is achieved, facilitating uniform impregnation and confinement of Na within the matrix pores promoted by the chemical interaction between Na and the matrix. The unique matrix's surface characteristic can divert the Na deposition from the skeleton towards the Na reservoirs within the pores, suppressing the volume change and mossy/dendritic Na growth. A stable Na cycling behavior is demonstrated in carbonate electrolyte without any additives at a high capacity up to 3 mAh cm −2 with a current density up to 2 mA cm −2 . Moreover, electrochemical measurements of a full cell made of the Na composite matrix anode clearly reveal the superior performance at high rate (5C) over that using bare Na metal. Abstract : A chemically engineered copper foam matrix, specifically oxygen‐treated copper (O‐treated Cu) matrix, which possesses cylindrical core–shell skeleton, serves as a highly stable host for metallic sodium (Na) anodes. This unique structure significantly suppresses the volume change and mossy/dendritic Na growth, contributing to a stable cycling behavior with flat voltage profile and low‐voltage hysteresis at a relatively high current density in carbonate electrolyte without any additives.